Adaptation of the Epic Legend of Siegfried: from Archetypal Hero Myth to Film - Solomonik-Pankrashova, Tatyana; Lobinaitė, Viktorija (Respectus Philologicus, 2016)
According to the psychic concept of adaptation, the original manifests itself as an archetype in culture. The film producer who employs archetypal hero myth creates yet another version of myth. A medieval narrative – a secularised sacred narrative – is translated into a cinematic narrative by a gallery of images. This kind of translation reveals similar semiotic complexity to that of the original. The film producer imitates the art of the medieval epic singer and remains faithful to the spirit of myth. This paper aims at deciphering the symbolic world of The Nibelungen: Siegfried (Die Nibelungen: Siegfried), a silent film created by Fritz Lang (1924). The novelty of the research lies in comparing the artistic expression of the film producer with the poetic expression of the medieval epic minstrel. The authors’ argument proceeds as follows: (1) consider the archetypal hero myth – its plot, theme, and motifs – as narratologically embedded in the adaptation of the epic legend of Siegfried; (2) reveal the interaction between the formulaic structure of the intertitles and oral epic poetry; (3) highlight mimesis as the imitative representation of the sacred world from the perspective of the symbolic world created in the film.
Keywords: Adaptation; Intersemiotic Translation; Intertextuality; Archetype; Oral Epic Poetry